An investigation into accounting students’ preliminary comprehension of auditing / Nur Farahah Mohd Pauzi … [et al.] - Mohd Pauzi, Nur Farahah; Karim, Mohd Syazwan; Shamsudin, Adriana; Abdul Fatah, Muhammad Mukhlis; Mamat, Siti Nurulhuda (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Audit has a critical function in identifying fraud that has taken place in the corporate sectors and in producing high-quality audit reports that help management make decisions. Despite the fact that the audit course is one of the core courses in the university-level accounting program, there are indications that accounting students do not have a good understanding of the audit profession. This study aims to ascertain the preliminary understanding of auditing among accounting students in regard to a few crucial elements. Semi-structured interviews with fifty students who are in their second-year Bachelor of Accountancy studies from a local university in Melaka were conducted. Findings of the study indicated that before taking the audit course, the undergraduates did not have a thorough understanding of audit. Despite having rudimentary understanding of the goals of auditing and how it greatly benefits the organizations, students did not have a comprehensive grasp of auditing.